Proposal for local SAR safety margin in pediatric neuro-imaging using 7 T MRI and parallel transmission - Dudysheva, N; Luong, M; Amadon, A; Morel, L; Touz, N Le; Vignaud, A; Boulant, N; Gras, V (Physics in medicine & biology, 2025)
Objective. Ultra-high field MRI with parallel transmission (pTx) provides a powerful neuroimaging tool with potential application in pediatrics. The use of pTx, however, necessitates a dedicated local specific absorption rate (SAR) management strategy, able to predict and monitor the peak local SAR (pSAR 10g ). In this work, we address the pSAR 10g assessment for an in-house built 7 T 16Tx32Rx pediatric head coil, using the concept of virtual observation points (VOPs) for SAR estimation. Approach . We base our study on full-wave electromagnetic simulations performed on a database of 64 numerical anatomical head models of children aged between 4 and 16 years. We built VOPs on different subsets of this database of N = 2 up to 30 models, and cross-validated the pSAR 10g prediction using non-intersecting subsets, each containing 30 models. We thereby propose a minimum anatomical safety factor (ASF) to apply to the VOP set to enforce safety, despite intersubject variability. Our analysis relies on the computation of the worst case SAR to VOP-SAR ratio, independent of the pTx RF excitation. Main results. The interpolation model provides that the minimum ASF decreases as 1 + 5.37 ⋅ N − 0.75 with N . Using all 64 models to build VOPs leads to an estimated ASF of 1.24 when considering the VOP validity for an infinite number of subjects. Significance. We propose a general simulation workflow to guide ASF estimation and quantify the trade-off between the number of numerical models available for VOP construction and the safety factor. The approach would apply to any simulation dataset and any pTx setup.